Identification of Hub Genes Associated With Progression and Prognosis in Patients With Bladder Cancer - Yan, Xin; Liu, Xiao-Ping; Guo, Zi-Xin; Liu, Tong-Zu; Li, Sheng (Frontiers in Genetics, 2019)
Given that most bladder cancers (BCs) are diagnosed in advanced stages with poor prognosis. Therefore, this study aims to find novel biomarkers associated with the progression and prognosis in patients with BC. 1,779 differentially expressed genes (DEGs) between BC samples and normal bladder tissues were identified in total. Then, 24 DEGs were regarded as candidate hub genes by constructing protein-protein interaction (PPI) network and random forest model. Among them, 6 genes (BUB1B, CCNB1, CDK1, ISG15, KIF15, and RAD54L) were eventually identified by using five analysis methods (one-way Analysis of Variance analysis, spearman correlation analysis, distance correlation analysis, receiver operating characteristic curve and expression values comparison), which were correlated with the progression and prognosis of BC. Moreover, the validation of hub genes was conducted based on GSE13507, Oncomine, and CBioPortal. Results of univariate Cox regression analysis showed that the expression levels of all the hub genes were influence features of overall survival (OS) and cancer specific survival (CSS) based on GSE13507, and we further established a 6-gene signature based on the expression levels of the six genes and their Cox regression coefficients. This signature showed good potential for clinical application suggested by survival analysis (OS: Hazard Ratio = 0.484, 95%CI: 0.298-0.786; P = 0.0034; CSS: Hazard Ratio =0.244, 95%CI: 0.121-0.493, P < 0.0001) and decision curve analysis. In conclusion, our study indicates that 6 hub genes have great predictive value for the prognosis and progression of BC, and may contribute to the exploration of further basic and clinical research of BC. Key words: bladder cancer, hub genes, survival analysis, enrichment analysis, prognosis, bioinformatics